COUNTERPRODUCTIVE WORK BEHAVIOR. COMPARISON OF THE PUBLIC AND PRIVATE SECTOR - Szostek, Dawid (Journal of Positive Management, 2019)
Purpose: The main purpose of the article is to verify a hypothesis that the public sector employees tend to engage in counterproductive behavior (CWB) at work more often than the private sector employees. An additional purpose is to present results of the research relating to frequency of engagement of employees in CWB in Poland. Methodology: The research was conducted in 2017 with the use of an online questionnaire method with respect to 535 employees from all regions of Poland. The data were analysed with the use of IBM SPSS application. Findings: Based on analysis of the research results (an analysis of frequency and Pearson’s chi-square coefficients) it has been found that there are no grounds for rejection of the hypothesis. This relationship was also observed in relation to particular manifestations, categories and dimensions of these behaviors. Implications/limitations: The research paper includes precious hints for managers working mainly in the public sector. Considering the research results, they should undertake particularly active CWB risk reducing activities in their organizations. It is also necessary to monitor appearance of such behaviors on an ongoing basis as well as identify reasons for such behaviors. The main limitations of the research include biased character of the sample resulting from its non-random selection and limited control over the process of research resulting from a method of data collection. A future research should involve a representative sample with the use of quantitative and qualitative methods, which will allow to extend the level of analysis and identify reasons for differences in manifestation of CWB by employees of both sectors. Originality/value: The research paper fills a gap in the literature relating to differences in tendencies to manifest CWB among the public and private sector employees in Poland. Despite the fact that the problem has already been emphasized by various authors, there are no comprehensive research results concerning the same.